Vitamin D-related genes and cardiometabolic markers in healthy children: a Mendelian randomisation study. Issue 10 (28th May 2020) - Lopez-Mayorga, Ania; Hauger, Hanne; Petersen, Rikke A.; Vogel, Ulla; Damsgaard, Camilla T.; Lauritzen, Lotte
Abstract: Observational studies show associations between low serum 25-hydroxyvitamin D (25(OH)D) and cardiometabolic risk markers. This Mendelian randomisation study examined associations between cardiometabolic markers in children and SNP in genes related to vitamin D metabolism ( DHCR7 ; group-specific complement ( GC ); cytochrome P450 subfamily IIR1 ( CYP2R1 ); and CYP24A1 ) and action ( CYP27B1 and VDR ). In 699 healthy 8–11-year-old children, we genotyped eleven SNP. We generated a genetic risk score based on SNP associated with low 25(OH)D and investigated associations between this and blood pressure, plasma lipids and insulin. Furthermore, we examined whether SNP related to vitamin D actions modified associations between 25(OH)D and the cardiometabolic markers. All GC and CYP2R1 SNP influenced serum 25(OH)D. A risk score based on four of the six SNP was associated with 3·4 (95 % CI 2·6, 4·2) mmol/l lower 25(OH)D per risk allele ( P < 0·001), but was not associated with the cardiometabolic markers. However, interactions were indicated for the three VDR SNP ( P interaction < 0·081) on associations between 25(OH)D and TAG, systolic blood pressure and insulin, which all decreased with increasing 25(OH)D only in major allele homozygotes ( β –0·02 (95 % CI –0·04, –0·01) mmol/l; β –0·5 (95 % CI –0·9, –0·1) mmHg; and β –0·5 (95 % CI –1·4, 0·3) pmol/l, respectively). In conclusion, genetic variation affected 25(OH)D substantially, but the genetic score was not associated with cardiometabolic markers in children. However, VDR polymorphisms modified associations with vitamin D, which warrants further investigation of VDR 's role in the relationship between vitamin D and cardiometabolic risk.